1997
DOI: 10.1128/aem.63.7.2607-2612.1997
|View full text |Cite
|
Sign up to set email alerts
|

Association of multiple-antibiotic-resistance profiles with point and nonpoint sources of Escherichia coli in Apalachicola Bay

Abstract: A total of 765 Escherichia coli isolates from point and nonpoint sources were collected from the Apalachicola National Estuarine Research Reserve, and their multiple-antibiotic-resistance (MAR) profiles were determined with 10 antibiotics. E. coli isolates from point sources showed significantly greater resistance (P < 0.05) to antibiotics and higher MAR indices than isolates from nonpoint sources. Specifically, 65 different resistance patterns were observed among point source isolates, compared to 32 among no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
80
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(93 citation statements)
references
References 24 publications
11
80
0
Order By: Relevance
“…MST emerged at the end of the 20th century (Wiggins, 1996;Parveen et al, 1997;Hagedorn et al, 1999;Bernhard & Field, 2000a;Harwood et al, 2000) as an attempt to determine the dominant sources of fecal contamination in environmental waters Field & Samadpour, 2007;Stoeckel & Harwood, 2007;Harwood et al, 2009). The impetus for emergence of this research area derives from (1) the effort to determine the extent to which fecal source (e.g.…”
Section: Mst and Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…MST emerged at the end of the 20th century (Wiggins, 1996;Parveen et al, 1997;Hagedorn et al, 1999;Bernhard & Field, 2000a;Harwood et al, 2000) as an attempt to determine the dominant sources of fecal contamination in environmental waters Field & Samadpour, 2007;Stoeckel & Harwood, 2007;Harwood et al, 2009). The impetus for emergence of this research area derives from (1) the effort to determine the extent to which fecal source (e.g.…”
Section: Mst and Applicationsmentioning
confidence: 99%
“…The basic premise of MST is that certain fecal microorganisms are strongly associated with particular hosts and that identified attributes of these host-associated microorganisms can be used as markers for fecal contamination from the host. The utility of two basic strategies have been tested (1) library-dependent analyses that required the collection and typing of many FIB isolates for some identifying attribute, including antibiotic resistance (Parveen et al, 1997;Harwood et al, 2000), carbon source utilization (Hagedorn et al, 1999), or genetic type (Parveen et al, 1999;Moore et al, 2005) and (2) library-independent analyses that target a particular feature of a specific bacterial species or type, for example, a variable region of the 16S rRNA gene of Bacteroidales (Bernhard & Field, 2000b).…”
Section: Mst and Applicationsmentioning
confidence: 99%
“…Sample preparation and bacteriological tests of E. coli were performed by standardized procedures (American Public Health Association 1984Parveen et al 1997). In brief, all samples were streaked onto MacConkey agar (Difco) and incubated for approximately 16-18 h at 37°C.…”
Section: Isolation and Identification Of E Colimentioning
confidence: 99%
“…Multiple antibiotic resistance (MAR) typing, using of single or multiple concentrations of antibiotic, is a method that has been used to differentiate sources of E. coli and faecal streptococci by testing bacterial resistance to antibiotics commonly associated with human and animal treatment, as well as with animal feed (Cooke 1976;Kaspar et al 1990;Wiggins 1996;Parveen et al 1997;Parveen and Tamplin 1998;Hagedorn et al 1999;Wiggins et al 1999Wiggins et al , 2003Harwood et al 2000;Kelsey et al 2003). Similar to other reports (Cooke 1976;Kaspar et al 1990), we previously found that E. coli isolated from human source were more resistant to antibiotics than nonhuman source isolates (Parveen et al 1997). We also found that discriminant analysis (DA) of MAR profiles correctly classified 82% of human isolates (Parveen and Tamplin 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it confounds our ability to link them to sources and potentially creates a disconnect between indicator bacteria concentration and pathogen presence in environmental waters. Many methods have been used to differentiate strains of indicator bacteria, including ribotyping and antibiotic resistance patterns (Parveen et al, 1997;Harwood et al, 2000;Anderson et al, 2006) as well as amplification of repetitive DNA sequences (Dombek et al, 2000;Johnson et al, 2004;Ishii et al, 2006), in order to investigate the influence of population structure on the ecology of persistent indicator bacteria.…”
Section: Introductionmentioning
confidence: 99%